Terapan Konsep Fun Experience dalam Desain Interior Perpustakaan Umum di Kota Probolinggo - Angga Jesslyn; Mariana Wibowo (Intra, 2019)
These day the development of libraries in Indonesia is still relatively low, followed by the interest of Indonesian public readers that is also the same. The library is one of the most accurate and trusted information centers, but most people choose to get information from the internet. This is due to the condition of the library which is uncomfortable, boring, and lacks of facilities, including public libraries in the Probolinggo City. The interior of the library has a very important function and role for the people who come to visit it. A library must be supported with a comfortable and pleasant place, so visitor will be interested to come and go to the library. The method used in this interior design uses the design thinking process according to Hasso Plattner which consists of 6 stages, namely: understanding, observing, point of view, ideate, prototype, and test. The interior design takes the concept of “a Fun Experience in Education” which is intended to replace the image of boring library into fun and elevate the culture of the City of Probolinggo with the tagline "Kota 1000 taman" which aims to increase the level of interest in reading among Probolinggo people from childrens to adults with entertainment facilities but still educative. The design equipped with a reading and playing room for children, an adult reading room equipped with an outdoor area, an audio visual room, a multifunctional area, a café and a garden.